Elementary topology and applications - Borges, Carlos R. (New Jersey World Scientific, 2021)
"The textbook is a very good start into the mathematical field of topology. A variety of topological concepts with some elementary applications are introduced. It is organized in such a way that the reader gets to significant applications quickly. This revised version corrects the many discrepancies in the earlier edition. The emphasis is on the geometric understanding and the use of new concepts, indicating that topology is really the language of modern mathematics"--
Includes bibliographical references and index.
Keywords: Topology